A comparative sizing analysis of a renewable energy supplied stand-alone house considering both demand side and source side dynamics - Elma, Onur; Selamogullari, Ugur Savas (ELSEVIER SCI LTD, 2012)
Solar and wind energy use to supply the electrical demand of a stand-alone residential house is investigated. Combining solar and wind energy sources provide more reliable power source for stand-alone applications since they complement each other. Backup units (battery/supercapacitor) are also needed for uninterrupted energy. For a proper backup sizing in such systems, high resolution load data, wind speed and solar radiation data must be used as compared to the use of hourly averaged data found in literature. In this study, high resolution data on both load side and source side are collected experimentally. Then, collected data used as input to system simulations in Matlab/Simulink for sizing the backup in the considered hybrid power system. Backup state of the charge (SOC) is used as decision criteria. It is shown that, when load and source dynamics are considered, approximately 10% less backup size is required compared to backup size found with hourly averaged values. The study shows the importance of data resolution on backup sizing in such systems and could be a guide for renewable energy system designers. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Hybrid renewable energy systems; Stand-alone house; Dynamic load data; Dynamic solar radiation data; Dynamic wind data; Sizing study; SYSTEMS-APPROACH; WIND; POWER; PV; DESIGN; SOLAR; OPTIMIZATION; METHODOLOGY; SIMULATION; ARRAY; Energy & Fuels; Engineering